Pengalaman Merek dan Keterlibatan Konsumen dalam Meningkatkan Niat Beli Produk Zara - Falren Angelyn; Richard Andrew (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The fashion retail brands in Indonesia have shown a significant downward trend, particularly with well-known fashion brands like Zara. This decline reflects changes in several factors influencing consumers' purchase intentions, such as brand experience and consumer involvement. This study aims to examine the influence of brand experience and consumer involvement on the purchase intention of Zara products. The research design applied in this study is quantitative with a descriptive approach. Non- probability sampling was used due to challenges in randomly reaching all Zara consumers, as the exact number of visitors could not be accurately determined. The sampling technique applied was purposive sampling, with a total sample of 150 respondents. Based on the research results, it can be concluded that Brand Experience has significant effect on the Purchase Intention of Zara products, and Consumer Involvement also has significant effect on the Purchase Intention of Zara products.